Influence of water availability on the photosynthetic behavior of Portulaca oleracea L. - Bittencourt, Priscila Pires (2018)
Crassulacean acid metabolism (CAM) and the C4 pathway are photosynthetic adaptations that significantly improve plant water use efficiency (WUE). These two CO2-concentrating mechanisms (CCMs) share many similarities, including the pre-fixation of CO2 as organic acids via phosphoenolpyruvate carboxylase (PEPC) and the subsequent decarboxylation of these acids near the active site of Rubisco. The simultaneous occurrence of both CCMs in the same tissues has long been regarded as biochemically conflicting; however, the existence of Portulaca species that can switch between C4 and CAM pathways within a single leaf challenges this assumption. By monitoring anatomical traits, photosynthetic parameters, nocturnal acid accumulation and transcript abundance of C4- and CAM-related genes, this study aimed to characterize the drought induced changes in CAM expression in both leaf and stem tissues of Portulaca oleracea. CAM was shown to be expressed in an entirely facultative fashion in leaves whereas both ontogenetic and environmental cues seem to control CAM induction in the stem tissues. Data revealed that depending on the environmental conditions and plant age, P. oleracea stems can perform either C3 or CAM, but not C4 photosynthesis. Gas exchange and chlorophyll a fluorescence analysis suggested that the daytime decarboxylation of the organic acids accumulated overnight in CAM- performing leaves supplied CO2 to Rubisco behind closed stomata at sufficient levels to maintain the photosynthetic apparatus integrity and functioning even after prolonged drought exposure. Overall, no marked anatomical changes were observed in P. oleracea leaves or stems during the CAM induction, suggesting that gene expression and metabolism reprogramming may account for most of the C4-to-CAM and C3-to-CAM transition in leaves and stems, respectively. Gene expression data also indicated that the switch between C3 and CAM pathways in the stems requires the transcriptional regulation of a more extensive set of CCM-related genes than the C4-to-CAM transition in the leaves. Altogether, our findings reveal a remarkable photosynthetic plasticity in P. oleracea and provide important clues about the mechanisms behind the compatibility between the C4 and CAM pathways in this plant species